Ewolucja roli i funkcji sejmu i senatu w systemie krajowej polityki europejskiej w okresie przedakcesyjnym - Michał Dulak (Ksiegarnia Akademicka Publishing, 2021)
The national parliament is crucial institution in a contemporary European states, which guarantees a legitimacy of a power and regime. At the same time, the effectiveness of a parliament is one of the most important hallmark of a democratic political system. The democratic legitimacy, which comes from a national parliament is one of the sphere of the national system of implementing European policy. The author, using the system approach in European studies research, analyze the evolution of the role and functions of the Polish Sejm and Senate in the pre‑accession period, i.e. before the year 2004. The role of Polish parliament is analyzed through the two research perspectives – historical and functional. In this way it is clearly observed a growing role of the Sejm and Senate in the relations with other political institutions within a national system of implementing European policy.